2022
DOI: 10.3389/fimmu.2022.941071
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cells and Macrophages in the Pathogenesis of Psoriasis

Abstract: Psoriasis is a chronic inflammatory skin disease characterized by scaly indurated erythema. This disease impairs patients’ quality of life enormously. Pathological findings demonstrate proliferation and abnormal differentiation of keratinocytes and massive infiltration of inflammatory immune cells. The pathogenesis of psoriasis is complicated. Among immune cells, dendritic cells play a pivotal role in the development of psoriasis in both the initiation and the maintenance phases. In addition, it has been indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(45 citation statements)
references
References 131 publications
1
42
0
2
Order By: Relevance
“… 9 Some studies have found that macrophages contribute to the pathogenesis of psoriasis, especially in the initiation stage. 10 In addition, T cells and neutrophils play an important role in the occurrence and development of psoriasis. 11 , 12 Thus, psoriasis and immunity are inseparable and it is necessary to reveal the immune cell spectrum of psoriasis mice.…”
Section: Introductionmentioning
confidence: 99%
“… 9 Some studies have found that macrophages contribute to the pathogenesis of psoriasis, especially in the initiation stage. 10 In addition, T cells and neutrophils play an important role in the occurrence and development of psoriasis. 11 , 12 Thus, psoriasis and immunity are inseparable and it is necessary to reveal the immune cell spectrum of psoriasis mice.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the infiltration of M1-Mø is another key characteristic of psoriasis. Previous studies have shown that the infiltration of M1-Mø greatly elevates the expression of inflammatory cytokines such as interleukins and TNF-α, which triggers psoriasis by stimulating the proliferation and inflammation of keratinocytes (Kamata and Tada, 2022). To date, little is known about the regulatory effects of ELE on Mø.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated expression of M1-Mø is another key characteristic of psoriasis, it has been found that various inflammatory cytokines such as ILs and TNF-α secreted by M1-Mø contribute to psoriasis by triggering inflammation in keratinocytes (Kamata and Tada, 2022). We therefore stimulated Mø using LPS/INF-γ to obtain M1-Mø in vitro and then examined the effects of ELE on the gene expression of key inflammatory cytokines in M1-Mø.…”
Section: Ele Indirectly Attenuates Keratinocytes Inflammation By Medi...mentioning
confidence: 99%
“…Although psoriasis is predominately a T-cell mediated disease, infiltration of monocytes/macrophages has been well characterized ( Vestergaard et al, 2004 ; Kamata and Tada 2022 ). A significant increase in 15-HETE was detected in monocytes from patients with psoriatic arthritis ( Wójcik et al, 2019 ).…”
Section: Alox15b In Inflammation and Diseasementioning
confidence: 99%